1987
DOI: 10.1111/j.1600-065x.1987.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Protein 1B236/Myelin‐Associated Glycoprotein (MAG) Defines a Subgroup of the Immunoglobulin Superfamily

Abstract: We have reviewed the structure and properties of the neural protein 1B236/MAG. This molecule consists largely of five Ig-like domains separated from its carboxyl terminal tail by a single membrane-spanning region. Two forms of the protein differ in the length and sequence of the carboxyl terminus: these are encoded by alternatively spliced mRNAs that are differentially expressed during postnatal neural development. The Ig-like domains of 1B236/MAG are unusual in having structural similarities to Ig V domains b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…This function was first proposed on the basis of MAG's biochemical properties and enrichment in myelin subfractions (21,22). This hypothesis was subsequently supported by several immunocytochemical studies, which demonstrated MAG's enrichment in periaxonal regions of central nervous system (CNS) and peripheral nervous system (PNS) myelin internodes (28), and which showed a strict correlation between the presence of MAG in periaxonal membranes and the formation and maintenance of the periaxonal space during Schwann cell remyelination in Quaking mice (33,35).Several laboratories have deduced the amino acid sequence ofCNS MAG from cDNA clones (1,14,15,26) and have identified MAG as a member of the immunoglobulin gene superfamily (37). Amino acid sequence homologies between the extracellular domains of MAG and those of other 1.…”
mentioning
confidence: 90%
“…This function was first proposed on the basis of MAG's biochemical properties and enrichment in myelin subfractions (21,22). This hypothesis was subsequently supported by several immunocytochemical studies, which demonstrated MAG's enrichment in periaxonal regions of central nervous system (CNS) and peripheral nervous system (PNS) myelin internodes (28), and which showed a strict correlation between the presence of MAG in periaxonal membranes and the formation and maintenance of the periaxonal space during Schwann cell remyelination in Quaking mice (33,35).Several laboratories have deduced the amino acid sequence ofCNS MAG from cDNA clones (1,14,15,26) and have identified MAG as a member of the immunoglobulin gene superfamily (37). Amino acid sequence homologies between the extracellular domains of MAG and those of other 1.…”
mentioning
confidence: 90%
“…MAG is a minor component of both CNS and PNS myelin, comprising approximately 0.1 % of the total myelin proteins in the PNS [for review see, 15,16]. The completely gly cosylated protein contains approximately 30% carbohydrate in a covalent linkage and has an apparent molecular weight of approx imately 100 kD.…”
Section: Introductionmentioning
confidence: 99%
“…These include neural cell adhesion molecule (N-CAM) ~ (Barthels et al, 1987;Cunningham et al, 1987), myelinassociated glycoprotein (MAG) (Lai et al, 1987;Salzer et al, 1987), L1 (Moos et al, 1988), Po (Lemke et al, 1988), contactin (Ranscht, 1988)-which are expressed in vertebrates-and two recently identified insect proteins, fasciclin II (Harrelson and Goodman, 1988) and amalgam (Seeger et al, 1988). With the exception of Po, they contain C2-type Ig domains, and their sequence similarity extends in some cases beyond the Ig-like region (Harrelson and Goodman, 1988).…”
mentioning
confidence: 99%
“…It has been proposed (Lai et al, 1987;Harrelson and Goodman, 1988) that a common, phylogenetically ancient role of C2-type domains may be to mediate cell adhesion or recognition phenomena during nervous system development. Another common trait shared by N-CAM, LI, and MAG is the presence of the L2/HNK-1 carbohydrate determinant .…”
mentioning
confidence: 99%